Hijacked justice : dealing with the past in the Balkans - Subotic, Jelena (Cornell University Press, 2009)
What is the appropriate political response to mass atrocity? In Hijacked Justice, Jelena Subotic traces the design, implementation, and political outcomes of institutions established to deal with the legacies of violence in the aftermath of the Yugoslav wars. She finds that international efforts to establish accountability for war crimes in the former Yugoslavia have been used to pursue very different local political goals.Responding to international pressures, Serbia, Croatia, and Bosnia have implemented various mechanisms of "transitional justice"-the systematic addressing of past crimes after conflicts end. Transitional justice in the three countries, however, was guided by ulterior political motives: to get rid of domestic political opponents, to obtain international financial aid, or to gain admission to the European Union. Subotic argues that when transitional justice becomes "hijacked" for such local political strategies, it fosters domestic backlash, deepens political instability, and even creates alternative, politicized versions of history. That war crimes trials (such as those in The Hague) and truth commissions (as in South Africa) are necessary and desirable has become a staple belief among those concerned with reconstructing societies after conflict. States are now expected to deal with their violent legacies in an institutional setting rather than through blanket amnesty or victor's justice. This new expectation, however, has produced paradoxical results. In order to avoid the pitfalls of hijacked justice, Subotic argues, the international community should focus on broader and deeper social transformation of postconflict societies, instead on emphasizing only arrests of war crimes suspects.